Esensi Hukum dalam Perjanjian Kontrak Kerja Pembangunan Asrama MAN 1 Kota Gorontalo Berdasarkan Pasal 1313 Kitab Undang-Undang Hukum Perdata - Iqbal F. Ibrahim; Mutia Cherawaty Thalib; Zulfikar Sarson (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The problems that occurred at MAN 1 Gorontalo City are closely related to the construction work contract agreement whose object is dormitories as one of the programs of the Ministry of Religion of the Republic of Indonesia which is intended for every school with madrasa status throughout Indonesia. Based on the data, it turns out that work that is already 30% in progress can be canceled because unexpected things happen, such as high rainfall in Gorontalo in September 2021 which resulted in work not being able to continue for some time. Apart from that, it turned out that 80% of the workers used by the contractor were Javanese and because the conditions and atmosphere at that time were still during the pandemic, the workers from Java could not go back to Gorontalo because the island of Java was in lockdown status. This is the reason why the Head of Development of Man 1 Dormitory, Gorontalo City, canceled the work contract because of the contract being castrated, in this case there was a target that was not achieved due to the condition of the workers, weather, and so on.